The Impact of a Health Education Program on Fear of Falling and Fall Risk in Elderly People from UATI: A Clinical Trial - Leal, Thailane Kelli; Gomes, Glaucia Sá Brandão Freitas; Moura, Ricardo Silva; Oliveira-Silva , Iransé; Oliveira, Luís Vicente Franco; Brandão, Glauber Sá (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Aging leads to morphofunctional changes that trigger a decline in functional mobility and an increased risk of falls. In light of the above, the present study aims to test the hypothesis that a health education program reduces the fear of falling and the risk of falls in elderly individuals from a University for the Third Age, who do not exhibit cognitive decline and are capable of performing physical tests and responding to questionnaires. This is a longitudinal, experimental study, conducted through a single-arm clinical trial, of the before-and-after type within the same group and with randomization of the evaluator groups, carried out from October to December 2023, in the northeastern region of Brazil. To assess the fear of falling, the Falls Efficacy Scale-International-Brazil (FES-I-BRASIL) was used, and for the evaluation of functional mobility, the Timed Up and Go test was employed. (TUG). The intervention lasted eight weeks, conducted over two days a week, consisting of in-person activities and activities carried out in the homes of the elderly. The health education program took place through theoretical and practical classes related to fall prevention activities and physical exercise, as well as home activities using educational booklets. Out of fifty potential participants, thirty-three (average age 71 ± 6.3 years) were selected, with 99.7% being female. The elderly showed a significant improvement in functional mobility (p = 0.02) and fear of falling (p = 0.01) after the health education program intervention; however, when dichotomized into age strata, it was possible to identify that only the group of elderly individuals aged 70 years or older showed a significant improvement in functional mobility (p < 0.01). This study suggests that a health education program for the elderly improves functional mobility, resulting in a reduction in the risk of falls and the fear of falling.